A Comparative Study of Postgraduate Periodontology Curriculum in Iran and a Selected Number of American and Canadian Dental Schools - Ali Zarandi; Seyyed Moein Seyyed Sadrkhani (Kerman University of Medical Sciences, 2016)
Background & Objective: The main objective of this study was to survey the postgraduate periodontology course in Iran and compare its curriculum with that of selected dental schools in the United States and Canada Methods: This was a descriptive study First data were gathered based on the information available on the universities websites Then postgraduate periodontology curriculum of Tabriz University of Medical Sciences Iran was investigated and compared to that of Harvard University Boston University University of Maryland and University of Toronto The studied variables consisted of number of years of education dental education model education curriculum completed units number of hours of completed units Results: In all selected dental schools the overall curriculum was coursecentered with theoretical courses in the stomatology system accompanied with clinical courses Great emphasis was placed on research Harvard University provides academic research and clinical training the period of its course ranged from 45 to 57 months and the graduates received two periodontal degrees Nevertheless the main emphasis at the University of Toronto is clinical and research training and the duration of the period is 36 months and the training is provided in the form of surgical or nonsurgical treatment In the University of Maryland Baltimore the training consists of surgery correction and regeneration of oral tissue implantology and gingival surgery The Department of Periodontics of Tabriz University of Medical Sciences provides a curriculum similar to that of the University of Toronto Its training program consists of courses on implantology periodontics tissue engineering plastic surgery reconstructive surgery of the mouth This training program comprises 40 courses presented in 2784 hours Conclusion: It seems that filling the minds of the learners with medical physiopathological and stomatological topics reduces clinical activity and significantly reduces research and academic papers Thus the academic rating of dentistry schools in Iran can be improved through providing postgraduate periodontology courses similar to those provided by high ranking universities This can also render fellowship and postgraduate courses more efficient for Iranian students